The Gambia - From Entrepot to Exporter and Eco-tourism : Diagnostic Trade Integration Study for the Integrated Framework for Trade-related Technical Assistance to Least Developed Countries - World Bank (Washington, DC, 2012)
For decades, Gambia has served as a regional entrepot, using the river as a transportation link to the hinterland. Relatively low import taxes, well-functioning port and customs services, and limited administrative barriers reinforced Gambia's position as a trading center. About 80 percent of Gambian merchandise exports consist of re-exports to the sub-region goods imported into Gambia are transported unofficially into Senegal and beyond. Gambian economy and especially its public finances are highly dependent on this trade because imported goods destined for re-export pay the normal import duties. Recently, however, re-exports have declined due to a combination of tensions with Senegal, harmonization of import and sales taxes in the region, and improved port and customs operations in Senegal and other neighboring countries. The current re-export trade is unlikely to be sustainable, calling for a strategy to build growth on a more secure foundation. The report identifies directions for establishing a more sustainable foundation for the country's position as a gateway to the region by improving the transport system and reinforcing its efficient trade facilitation services, while recognizing the limited potential for growth. The study makes detailed recommendations on strengthening and diversifying domestic production of goods and services in the areas of tourism, groundnuts, other agriculture, and fishing, by improving the business climate as well as implementing sector-specific reforms.